Analysis of Diversity and Abundance Soil Insects in Taman Gumi Banten, Forest of Wanagiri Village, Buleleng - Ida Ayu Purnama Bestari; Ni Luh Putu Ananda Saraswati Saraswati; Ni Kadek Putri Adnyaningsih; I Made Oka Riawan; I Kadek Perdiana (Jurnal Pendidikan Biologi Undiksha, 2022)
The forest in Wanagiri Village about 1.055 ha, and almost 250 ha of that forest managed as “village forest”. Village forest is the forest that is used by villagers, and in addition to being a natural reservoir area and maintaining water availability. This research aims to explored diversity and abundance soil insects that play a role in maintaining soil fertility. Surface insects were collected using the pitfall trap method, while infauna or ground insects were collected using the core method. The site of this research consists of 8 plots each site with random purposive sampling. The results showed that macrofauna species were higher than infauna. The diversity Index of soil insects is in the low category (0.355987).